If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 166 = 2x + -3(6x + 18) Reorder the terms: 166 = 2x + -3(18 + 6x) 166 = 2x + (18 * -3 + 6x * -3) 166 = 2x + (-54 + -18x) Reorder the terms: 166 = -54 + 2x + -18x Combine like terms: 2x + -18x = -16x 166 = -54 + -16x Solving 166 = -54 + -16x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '16x' to each side of the equation. 166 + 16x = -54 + -16x + 16x Combine like terms: -16x + 16x = 0 166 + 16x = -54 + 0 166 + 16x = -54 Add '-166' to each side of the equation. 166 + -166 + 16x = -54 + -166 Combine like terms: 166 + -166 = 0 0 + 16x = -54 + -166 16x = -54 + -166 Combine like terms: -54 + -166 = -220 16x = -220 Divide each side by '16'. x = -13.75 Simplifying x = -13.75
| 6x^2+14x-9x-21= | | 7r+4=2r+20 | | -4/9z=-3/5 | | 4x-9=5x+4 | | -48-14x=-202 | | 2ix^2+x+15i=0 | | 4.5=2x+3 | | 2x=429 | | 3-5n+3n=35-72 | | 5(x+7y)-8(6+y)= | | 60x^2+120x=0 | | -7+2x=9 | | X^5+36x=0 | | X^2+5x^2+4=0 | | 20-3x=5+2x | | x+x+8=26 | | x-5=1-2x | | -6(x+5)-44=2-22 | | 20x^3+60x^2=0 | | -11+2x=7 | | y+63x^3-75x^2+18x=0 | | 2(-2)+4y=-8 | | 2x-12+6x-21=6x+21 | | y=63x^3-75x^2+18x | | -5/6w=-16.5 | | 2*3.14x=44 | | 4(7b-8)+8=-3+7(7b+3) | | 0.5(x-8)=20 | | .9x=8.1 | | 3x-5+2x=40 | | 1/2h*13=130 | | .1q-.2(3q+4)=-.3(5q+3) |